Evaluation of fluoride removal from water by hydrotalcite-like compounds synthesized from the kaolinic clay - Khaled Hosni; Ezzeddine Srasra (Химия и технология воды, 2011)
The present study investigates the fluoride sorption by Mg – Al – CO₃ prepared from a kaolinite as natural source of aluminium using two simple methods.